2008
DOI: 10.1540/jsmr.44.101
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of moderate-intensity exercise increases vascular NO bioavailability and attenuates adrenergic receptor-dependent and -independent vasoconstrictor response in rat aorta

Abstract: The present study investigated the effect of one bout of moderate-intensity exercise on the adrenergic receptor-dependent and -independent vasoconstrictor response in rat aortas, and the role of nitric oxide (NO) bioavailability on these vasomotor responses. One group of rats was submitted to a 60 min of exercise at approximately 60% of maximal exercise capacity on a treadmill (exercise group) and the other one was placed in the treadmill without running (control group). Immediately after this period, both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Bechara et al ( 7 ) showed that improvements in the vasodilator response occurred immediately after a single exercise session performed on a treadmill at 60% of maximal exercise capacity, directly related to an increase in the bioavailability of endothelial nitric oxide and attenuation of the maximal contractile response ( 8 , 9 ). This post-exercise response model is relevant to the development of post-exercise hypotension in humans, in which both hypertensive and normotensive subjects experience a reduction in blood pressure during the first minute after a single exercise session ( 10 - 12 ), which may continue for hours after the exercise session ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bechara et al ( 7 ) showed that improvements in the vasodilator response occurred immediately after a single exercise session performed on a treadmill at 60% of maximal exercise capacity, directly related to an increase in the bioavailability of endothelial nitric oxide and attenuation of the maximal contractile response ( 8 , 9 ). This post-exercise response model is relevant to the development of post-exercise hypotension in humans, in which both hypertensive and normotensive subjects experience a reduction in blood pressure during the first minute after a single exercise session ( 10 - 12 ), which may continue for hours after the exercise session ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current research, participants were obliged to continue moderate intensity training until they get exhausted. The average duration of running with moderate intensity in the current research was approximately 5.15 minutes (21).…”
Section: Discussionmentioning
confidence: 73%
“…More recently, it has been shown that the activity and the expression of the eNOS enzyme is increased by acute exposure of both endothelial cells and mice aorta exposed to shear stress and high levels of adrenergic agonists. In addition, this training was also able to increase endothelial secretion of calcium and release of nitric oxide, dependent on the calcium (21).…”
Section: Discussionmentioning
confidence: 90%
“…Vascular homogenates were prepared using liquid N 2 , centrifuged at 5,000 rpm for 5 min, and 10-μL aliquots of the supernatant were injected into a Sievers chemiluminescence analyzer (model 280; Sievers Instruments, Inc., Boulder, Colorado, USA) using VCl3 and HCl (at 95°C) as reductants as previously described 30,31. The results were normalized to the protein concentration.…”
Section: Methodsmentioning
confidence: 99%